2021
DOI: 10.3390/ijerph18189542
|View full text |Cite
|
Sign up to set email alerts
|

Media Representations of Science during the First Wave of the COVID-19 Pandemic: A Qualitative Analysis of News and Social Media on the Island of Ireland

Abstract: COVID-19 is arguably the most critical science communication challenge of a generation, yet comes in the wake of a purported populist turn against scientific expertise in western societies. This study advances understanding of science–society relations during the COVID-19 pandemic by analysing how science was represented in news and social media coverage of COVID-19 on the island of Ireland. Thematic analysis was performed on a dataset comprising 952 news articles and 603 tweets published between 1 January and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
0
3
0
1
Order By: Relevance
“…In contrast, the science of COVID-19 and its related topics ( Caulfield et al, 2021 ; O'Connor et al, 2021 ; Scheufele et al, 2021 ; Schück et al, 2021 ), such as pseudo-science and misinformation or fact-checking and correction were not central to COVID-19 representations. During the analysis period, the topic of science on COVID-19 constituted around 10% of the total data (stage 1: 11.32%, stage 2: 6.34%, stage 3: 6.78%).…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, the science of COVID-19 and its related topics ( Caulfield et al, 2021 ; O'Connor et al, 2021 ; Scheufele et al, 2021 ; Schück et al, 2021 ), such as pseudo-science and misinformation or fact-checking and correction were not central to COVID-19 representations. During the analysis period, the topic of science on COVID-19 constituted around 10% of the total data (stage 1: 11.32%, stage 2: 6.34%, stage 3: 6.78%).…”
Section: Discussionmentioning
confidence: 92%
“…For example, Kitzinger et al (2008) examined gender representations within science-related news stories published in Britain over a 6-month period and concluded that males were cited at a much higher frequency. This pattern has been observed within Finnish news coverage (Niemi and Pitkänen, 2017), Danish news media (Wien, 2014), Irish news media coverage (O'Connor, 2021), and Spanish news media (González et al, 2017). This lack of female representation can reinforce gendered stereotypes that females cannot be scientific experts (Carli et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 74%
“…Hal ini dapat digunakan sebagai sarana untuk menciptakan kepercayaan diri, penguatan diri, dan branding diri. Dalam mengatasi hal negatif pada psikologis penggunanya, media sosial juga berguna untuk menghilangkan keterasingan sosial bagi penggunanya (Charkawi, 2021;Cudo, 2020;O'connor, 2021;Seberger, 2021).…”
Section: Pendahuluanunclassified